2020
DOI: 10.3390/microorganisms8060890
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Responses of Phormidium ambiguum and Microcystis aeruginosa Under Diurnally Varying Light Conditions

Abstract: Two harmful cyanobacteria species (Phormidium ambiguum and Microcystis aeruginosa) were exposed to diurnal light-intensity variation to investigate their favorable and stressed phases during a single day. The photosynthetically active radiation (PAR) started at 0 µmol·m−2·s−1 (06:00 h), increased by ~25 µmol·m−2·s−1 or ~50 µmol·m−2·s−1 every 30 min, peaking at 300 µmol·m−2·s−1 or 600 µmol·m−2·s−1 (12:00 h), and then decreased to 0 µmol·m−2·s−1 (by 18:00 h). The H2O2 and antioxidant activities were paralleled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…As a representative, H. lacustris accumulated the maximum astaxanthin under oxidative stress, e.g., treatments of high light and FeSO 4 + SA, ~54.3% of total astaxanthin [19]. High light-induced oxidative stress is among the strongest inducers for secondary carotenoids in a wide range of photosynthetic organisms, from green algae to higher plants [50,51]. Effective oxidative adaptation has been widely preserved in oxygenic photosynthetic organisms during Earth's oxygenation.…”
Section: Oxidative Adaptation Has Been Widely Preservedmentioning
confidence: 99%
“…As a representative, H. lacustris accumulated the maximum astaxanthin under oxidative stress, e.g., treatments of high light and FeSO 4 + SA, ~54.3% of total astaxanthin [19]. High light-induced oxidative stress is among the strongest inducers for secondary carotenoids in a wide range of photosynthetic organisms, from green algae to higher plants [50,51]. Effective oxidative adaptation has been widely preserved in oxygenic photosynthetic organisms during Earth's oxygenation.…”
Section: Oxidative Adaptation Has Been Widely Preservedmentioning
confidence: 99%
“…When the bubbling, mechanical mixing, and reservoir drawdown‐like techniques are employed, cyanobacteria are subjected to undesirable light and temperature regimes via mixing the water layers or reducing the water depth. Notably, both low and high light intensities can negatively affect the growth of cyanobacteria (Hsieh et al, 2014; Muhetaer, Senavirathna, & Fujino, 2020). When direct sunlight is used, the light intensity can reach 1500 μmol m −2 s −1 photosynthetically active radiation (PAR) intensity.…”
Section: Introductionmentioning
confidence: 99%
“…As pivotal primary producers and pioneer species, they exhibit outstanding stress resilience [3]. Scientists have conducted numerous simulations on the response of cyanobacteria to extreme conditions, including polar regions [4], space radiation [5,6], a high-chlorine salt environment in the surface of Mars [7], Martian-like pure CO 2 atmosphere conditions [8], high temperature [5], and high light [9], in anticipation that it can become a pioneer species to transform outer planets and reserve bioenergy during disasters. Studies have demonstrated that cyanobacteria, especially Microcystis aeruginosa, survive in extreme environments, although oxidative stress is produced [10,11].…”
Section: Introductionmentioning
confidence: 99%